Advancing data-driven health research from the All of Us data training and engagement program. - Sadowski, Kristi; Tarver, DeBran; Burnette, Jennifer; Dillman, Allissa; Renfro, Regina; Gibson, LaFrancis; Bursey, Kelli; Bartlett, Laura; Bonds-Bishop, Nadine; Connor, Lisa; Flores-Rivera, Efraín; Joseph, Sarah; et al. (Journal of the Medical Library Association, 2026)
Background: Fulfilling a recognized need in data skills training for academic librarians, the National Library of Medicine and the National Institutes of Health All of Us Research Program collaborated to enhance academic library workers' skills in biomedical and public health data, as well as their library's research capacity, through the awareness and use of the All of Us Researcher Workbench. Case Presentation: The All of Us Data Training and Engagement Program for Academic Libraries (ALP) blended professional development training, hands-on learning, and peer-to-peer networking that focused on increasing knowledge of the All of Us Researcher Workbench. Activities were designed to build institution-wide, interdisciplinary awareness and interest in using the All of Us Researcher Workbench. A series of ongoing activities ensured sustained skill-building and collaboration, and included training for R, a program language used for statistical computing and data visualization. Program activities were intentionally designed to help grow institutional research capacity, enhance skills in biomedical and public health data, and promote meaningful use of the Researcher Workbench to campus communities. Conclusion: The ALP helped participants overcome barriers to data access and improve research infrastructure and successfully empowered 115 library professionals to leverage the All of Us Researcher Workbench for meaningful biomedical and public health research. Measured outcomes validate the success of the program and demonstrate how the ALP has positioned participating institutions for long-term success in biomedical and public health research. Institutions can build upon the foundation established through this case report to advance equitable, data-driven health research across academic landscapes.